The International Encyclopedia of Political Communication 2016
DOI: 10.1002/9781118541555.wbiepc156
|View full text |Cite
|
Sign up to set email alerts
|

Media Effects Theory

Abstract: Media effects include theories that explain how the mass media influence the attitudes and perceptions of audience members. First, this entry touches on the history of media effects. Second, it gives an overview of the main theories in this area. Finally, using three of the most recent theories within media effects, namely framing effects, agenda‐setting, and priming, the entry explains media effects theory and the psychological mechanisms involved in these three theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This creator-viewer relationship demonstrates the reflective influence communication and communicators have on each other [5,29]. It is widely reported that communication plays a role in cognition, which in any event within healthcare ought to be upheld to bioethical principles [30].…”
Section: Onomastic Analysismentioning
confidence: 77%
“…This creator-viewer relationship demonstrates the reflective influence communication and communicators have on each other [5,29]. It is widely reported that communication plays a role in cognition, which in any event within healthcare ought to be upheld to bioethical principles [30].…”
Section: Onomastic Analysismentioning
confidence: 77%
“…According to framing theory, the way an issue is portrayed in the media can have an influence over how it will be perceived and inferred by the audience (Gever, 2019). Frames in the media influence people's emotions, attitudes, and behaviors toward issues (Borah, 2016). Past research has also established a link between media messages and audience behavioral change (Bowen, 2013).…”
Section: Hypothesis 5b (H5b)mentioning
confidence: 99%
“…The basic framework that this study adopted is that of the general cluster media effects (Borah, 2016), wherein media consumption can influence the audience's mental state, psychology, and cultural awareness. This influence later on becomes motivation for the audience to perform an action related to what they have seen or experienced from the media (Griffin, 2012).…”
Section: From Rurouni Kenshin Fan To Kendoka: Finding the Connectionmentioning
confidence: 99%